Biological properties of a novel solution based on silver nanoclusters for arresting dentin caries - Molina, Gustavo Fabián; Cabalén, María Belén; Aranguren, Juan Pablo; Pino, Gustavo Ariel; Burrow, Michael Francis (Frontiers in Oral Health, 2024)
ObjectivesTo test the biological properties of a novel non-restorative treatment method for arresting dentin caries based on silver nanoclusters (AgNCls) synthesized in polymethacrylic acid (PMAA).MethodsSynthesis of AgNCls was performed by photoreduction of AgNO3 in PMAA with 355 nm/wavelength light. AgNCls/PMAA was characterized by absorption/fluorescence spectroscopy and optical and atomic force microscopy. The stability of the clusters in an aerated PMAA solution was evaluated by means of fluorescence spectroscopy. Cytotoxicity was assessed using the MTT assay and antibacterial effect was determined for minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and colony forming (CFU) of Streptococcus mutans (S. mutans) and Lactobacillus acidophilus (L. acidophilus). 38% Silver Diammine Fluoride (SDF) was used for the control groups.ResultsChemical and structural identity of the clusters did not change within 9 months; Cell viability of 92%–89% was found after 24–48 h respectively. MIC and MBC were determined from 1:16 and 1:8 dilutions, respectively. Log CFU counts of S. mutans, and L. acidophilus treated with AgNCls/PMAA (3.4 ppm of silver) were significantly lower than in the control groups and even lower than when the same bacterial strains were treated with SDF (15,525 ppm of silver).ConclusionsAgNCls/PMAA presented chemical stability, acceptable cytotoxicity, and a potential antibacterial effect for strains associated with caries lesions at very low concentrations of silver.